Innovative Learning Strategies in Social Sciences: The Merdeka Curriculum Experience at Madrasah Tsanawiyah - Diana Mardiati; Syafri Anwar; Darmansyah Darmansyah; Erianjoni Erianjoni; Fadilla Syahriani (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores social science teaching strategies implemented under the Merdeka Curriculum at Madrasah Tsanawiyah. The Merdeka Curriculum grants schools autonomy in designing educational approaches to meet specific student needs while aligning with overarching objectives. A qualitative case study approach was employed, incorporating interviews, observations, and document analysis to examine the strategies used by social science teachers at Madrasah Tsanawiyah. The research focused on understanding how educators navigate the curriculum's flexibility and address challenges. The findings reveal that teachers adopt diverse strategies tailored to their students’ needs, emphasizing creativity and engagement despite limited resources and time constraints. These strategies demonstrate educators' commitment to maximizing the potential of the Merdeka Curriculum while overcoming implementation barriers. The study provides valuable insights into the practical application of the Merdeka Curriculum in social science education, particularly in resource-limited contexts. It highlights the importance of teacher adaptability and innovation in achieving curricular goals. These findings have implications for curriculum development, professional growth initiatives, and the broader improvement of social science education. This research contributes to the understanding of curriculum autonomy by illustrating its implementation challenges and opportunities within Madrasah Tsanawiyah. Future studies could explore specific teaching strategies in greater depth, evaluate the curriculum's impact on student outcomes, and identify global parallels to enhance the effectiveness of autonomous educational models in diverse contexts.